Seller debt in acquisitions of private firms: a security design approach - Jansen, M; Phalippou, L; Noe, T (Oxford University Press, 2023)
We propose a security design model in which a potential acquirer approaches a firm with a value-add plan. The target has a single owner, who possesses private information: he alone knows whether his firm is compatible with the plan. The owner agrees that the acquirer will add value but believes that the value-add will not be as much as what the acquirer expects. Although the acquirer can choose any monotone limited liability security to offer along with cash, we show that, under general conditions, any security that is employed always takes the form of nonrecourse debt provided by the seller. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online